LUPIN MEAL UTILISATION IN AQUACULTURE FEEDS - Agung Sudaryono (JOURNAL OF COASTAL DEVELOPMENT, 1999)
The paper review nutritional value and production of lupin meal and its uses in aquaculture feeds. Feed is the major cost variable in a aquaculture system representing up to 60% of total operating costs. The utilization of cost effective feeds would improve profitability of a aquaculture business. Commercial aquaculture feeds have been traditionally based on fish meal as the main dietary animal protein source and soybean meal as the dietary plant protein source. Lupin meal as an alternative dietary protein source has a favorable amino acids profile as compared to soybean meal. Lupin meal is consistently available, cost effective, palatable and highly digestible to most species of fish. It has been demonstrated that lupin meal will replace a considerable amount of soybean meal with no loss in production and fish performance. Manganese and methionine levels must be considered when utilizing high level of lupin in aquaculture feeds. Lupin meal is comparable nutritionally with soybean meal, it is more cost effective.